Self-reliance or closure: Case study - Montejo, Pedro H. (Animo Repository, 1978)
In all the seven years of its existence, Sta. Monica High School has been dependent on the monthly subsidy given by the archdiocese. The director of the previous years and the principal did not bother themselves regarding the salary of the teachers and maintenance of the school plant and the school bus, even if the students cannot pay their tuition. Until they have realize just recently their mistake, when the Archbishop informed them that the Fordham Foundation has not renewed its grant and that the Archdiocesan Council decides to close the school if it cannot be self-reliant beginning the incoming school year. In solution to this problem, alternative actions were recommended by the writer on the latter part of the paper.